Development and validation of the TexCoMP model: A nonlinear framework for optimising slip-resistant walkway coatings in diverse environments - In-Ju Kim (PLoS ONE, 2026)
Background Slip-related accidents remain a significant safety concern in public walkways, healthcare facilities, and industrial environments, particularly under contaminated surface conditions. Although numerous studies have investigated slip resistance using friction measurements and statistical classification approaches, existing predictive models often rely on simplified linear relationships or data-driven algorithms that provide limited physical interpretability of tribological interactions. Objectives This study aims to experimentally evaluate the slip-resistance performance of coated ceramic walkway surfaces under varying environmental conditions and to develop an interpretable, nonlinear, predictive framework, termed TexCoMP (Texture-Coating-Material-Performance), that integrates coating properties, surface texture characteristics, and environmental contamination effects. Specific objectives are to: (1) compare four coatings across four ceramic tiles and three shoe types; (2) assess arid, damp, and foamy environmental impacts; and (3) identify optimal combinations for walkway safety per ANSI A137.1:2022 and ISO 5436:2021 standards. Methods Four coating materials (CM 1-CM 4) were applied to four ceramic tile surfaces (CT 1-CT 4) and evaluated using tribological testing under arid, damp, and foamy contamination conditions with three footwear materials. Surface texture parameters were characterised using roughness measurements, and dynamic friction coefficients (DFCs) were determined through controlled dynamic friction tests. A nonlinear predictive model incorporating coating material performance (CMP), surface texture modification (STM), and environmental factors (E) was developed and validated using statistical analysis and cross-validation across 144 experimental combinations (432 individual measurements). Results TexCoMP achieved a mean absolute error (MAE) of 0.03, a root mean square error (RMSE) of 0.04, a Pearson correlation ( R ) of 0.92, and an R 2 of 0.93, outperforming linear models by 22% in terms of RMSE under foamy conditions. The epoxy-CT4 pairing yielded a DFC of 0.62 ± 0.03 in damp conditions, 24% above the OSHA safety threshold of 0.5, indicating substantially reduced slip potential. Four-way ANOVA revealed highly significant interactions ( p < 0.001) with environmental condition as the dominant factor (partial η² = 0.47). Conclusions The proposed TexCoMP framework provides an interpretable tribological model for predicting slip resistance in coated walkway systems by integrating coating material properties, surface texture modification, and environmental contamination effects. The results demonstrate that coatings incorporating texture-enhancing particles can significantly improve friction performance under damp conditions. TexCoMP therefore offers a practical analytical tool for guiding coating selection and surface engineering strategies to reduce slip-related risks in built environments.